Cerebral Amyloid Angiopathy-Related Inflammation in the Immunosuppressed: A Case Report - Nelson, Thomas; Leung, Bo; Bannykh, Serguei; Shah, Kevin S.; Patel, Jignesh; Dumitrascu, Oana M. (Frontiers in Neurology, 2019)
Cerebral amyloid angiopathy-related inflammation (CAA-ri) is an immune-mediated disorder of the central nervous system characterized by an inflammatory response to amyloid-beta (Aβ) deposition within cerebral blood vessel walls. Immunosuppressive therapy is the mainstay of treatment. We present a case of CAA-ri in a subject already on immunosuppressive therapy after orthotopic heart transplantation (OHT). A 57-year-old man 8 months post-OHT for sarcoid cardiomyopathy developed headaches and staring spells while hospitalized for disseminated mycobacterial infection. His brain MRI revealed bi-hemispheric T2-weighted fluid-attenuated inversion recovery white matter hyperintensities and widespread microhemorrhages. Two weeks later, he developed gait ataxia and alterations in mental status, and repeat brain MRI showed more extensive confluent white matter hyperintensities. Leptomeningeal and cortex biopsy revealed changes consistent with amyloid angiitis, with perivascular and intramural histiocyte and lymphocyte collections. Mass spectroscopy confirmed Aβ deposition. Notably, the patient was on immunosuppression with daily 5 mg oral prednisone and tacrolimus before biopsy. After high-dose intravenous followed by oral corticosteroids, he demonstrated significant clinical and radiographic improvement. No relapse was noted despite the relatively rapid tapering of the prednisone therapy over 3 months, as mandated by his systemic infection. Despite the lack of a standard treatment protocol for CAA-ri, case series have reinforced the benefit of prolonged courses of glucocorticoids as single agent or in combination with other immunomodulatory agents. Hence, management of CAA-ri in patients with disseminated mycobacterial infections or OHT is challenging. Our case is unique, as review of existing literature has not revealed any similar cases of patients on chronic immunosuppression at the time of CAA-ri diagnosis, which one would expect to protect against this disorder. In addition, CAA-ri in association with cardiopulmonary sarcoidosis was not previously reported; however, a common immunopathogenic mechanism may exist.